Coexistência de aspectos relacionais e transacionais em alianças estratégicas internacionais marcadas pelo rígido controle de custos - Calvilho, Eduardo Magalhaes (Universidade do Vale do Rio dos Sinos, 2012)
The developing countries are presenting themselves as a good investment option to international companies which are aiming for expanding their busines area. The technological limitation of those countries added to the difficulties that the foreign companies have to access the local market make the International Strategic Alliances (ISA) become as a good option for companies of both nationalities. According to Booz & Company Consulting study, the Pre-salt exploration scenario will demand not only for high technology, but also for financial investments around US$ 500 billion on the Exploration and Production (E&P) sector. So that, understanding which points should be observed after the Strategic Alliances (SA) creation and when running an alliance will result in competitive advantage and in an additional chances of the organizations success. The literature points out to cultural divergence as an important issue to be considered on the alliances process formation. There is a close relation between the organization culture and its Governance structure and this defines principles and behaviors which guide the alliance management. (LANGFIELD-SMITH, 2008). The studies of Ness and Haugland (2005), Poppo and Zenger (2002) and Roath et al. (2002) indicated two governance structure dimensions, contract oriented (transactional) and relations oriented. To investigate how different organizational cultures (contractual or relational) interact in SA or in ISA were researched six alliances. These SA were established to perform specialized services to a governmental company. The author found out that all alliances had run on scenarios predominantly transactional. The cultural divergences between national and international companies didn’t seem to affect the alliances performance. The unbalance of power situation created by the governmental company resulted in costs raise to the alliances at the first time. To recover the revenue the alliances had to use opportunistic behaviors, by means of taking advantage of lack of details of the service contract, raising the ex post costs to the customer afterwards. In the end, the findings analysis led the author to identify three different ways how the alliances’ governance structure is established, defined by culture, by the situation or by the strategy.
Keywords: Opportunistic behaviors; Ex post costs; Governance; Culture; Strategic alliances; Comportamentos oportunistas; Custos Ex Post; Governança; Cultura; Alianças estratégicas; ACCNPQ::Engenharias::Engenharia de Produção